Herbal medicine Davaie Loban in mild to moderate Alzheimer's disease: A 12-week randomized double-blind placebo-controlled clinical trial. Issue 6 (December 2015) - Tajadini, Haleh; Saifadini, Rostam; Choopani, Rasool; Mehrabani, Mitra; Kamalinejad, Mohammad; Haghdoost, Ali Akbar
Highlights: Davaie Loban (DL) contains Cyperus rotundus L., Zingiber officinale, Acorus calamus L., Piper nigrum L., and Boswellia carterii . DL can improve memory in patients with mild-to-moderate Alzheimer's disease without any adverse reaction. It seems that the main mechanisms of action of DL in Alzheimer's disease are cholinergic effect, antioxidant activity and reduction of amyloid toxicity. Abstract: Objective: In traditional texts on herbal medicines, various medicinal plants have been noted to have beneficial effects on dementia and Alzheimer's disease. According to the traditional books Herbal medicine Davaie Loban (DL) has beneficial effects in Alzheimer's disease. The study aim was to determine the clinical efficacy of DL in patients with mild-to-moderate Alzheimer's disease. Design: Double blind randomized clinical trial. Setting: Shahid Beheshti University of Medical Sciences. Interventions: This included patients older than 50 years with mild to moderate Alzheimer's disease according to ADAS-cog (Alzheimer's Disease Assessment Scale-cognitive subscale; ADAS ≥ 12) and the Clinical Dementia Rating Scale Sum of Boxes (CDR-SOB; CDR ≤ 2). Twenty-four patients completed the study in DL group and 20 in placebo group. Main outcome measures: ADAS-cog and CDR-SOB were filled out for patients to define the improvement in memory over the study period. Results: At 4 weeks and 12 weeks there was significant difference in mean (SEM) ADAS-cog scores between DL and placebo groups and it was lower in DL group ( p < 0.001). At baseline, no significant difference was seen regarding mean (SEM) scores of CDR-SOB between DL and placebo groups ( p = 0.096). However, at 4 and 12 weeks there was significant difference in mean (SE) CDR-SOB scores between DL and placebo groups and it was lower in DL group ( p < 0.001). Conclusion: Our findings suggest that DL may be effective in improvement of memory in patients with mild-to-moderate Alzheimer's disease.